2006
DOI: 10.1159/000097003
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the Expression of ATP-Sensitive Potassium Channel Subunit mRNA after Acute Peripheral Nerve and Spinal Cord Injury

Abstract: ATP-sensitive potassium channels (KATP) are involved in the regulation of potassium homeostasis in the nervous system, and they may play an important role in acute peripheral nerve and spinal cord injury. Here, the expression of the KATP genes was monitored by reverse transcription polymerase chain reaction (RT-PCR) in the rat dorsal root ganglion, spinal cord and cerebral cortex following acute sciatic nerve and spinal cord injury. Electrophoresis of the RT-PCR products showed that in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
0
2
1
Order By: Relevance
“…However, our results showed that there is no change in channel expression for K ATP in the spinal cord under the rat formalin test. This result is different from Yin's report that Kir 6.2 mRNA expression was significantly increased after sciatic nerve injury [23]. This may have resulted from the difference between the inflammatory pain model and the neuropathic pain model in terms of K ATP channel involvement in the pain modulation process.…”
Section: Discussioncontrasting
confidence: 84%
“…However, our results showed that there is no change in channel expression for K ATP in the spinal cord under the rat formalin test. This result is different from Yin's report that Kir 6.2 mRNA expression was significantly increased after sciatic nerve injury [23]. This may have resulted from the difference between the inflammatory pain model and the neuropathic pain model in terms of K ATP channel involvement in the pain modulation process.…”
Section: Discussioncontrasting
confidence: 84%
“…In another study, both Kir6.1 and SUR2 mRNA were increased in the rats spinal cord 4 and 24 h after the acute spinal cord injury [24]. Our study observed that only Kir6.1 and SUR2 were increased in the cultured neurons after being exposed to Ab 1-42 for 24 h. The possible mechanism may be as follows: first, many studies had demonstrated the Kir6.2 existed in most neurons while the brain mitoK ATP channel may be composed of Kir6.1 [25,26].…”
Section: Discussionmentioning
confidence: 91%
“…In another study, both Kir6.1 and SUR2 mRNA were increased in the rat spinal cord 4 and 24 h after the acute spinal cord injury [25]. Our study observed that only Kir6.1 and SUR2 were increased in the cultured neurons after being exposed to Ab 1-42 for 24 h. Melamed-Frank reported that hypoxia can up-regulate the expression of Kir6.1 mRNA in vivo and vitro studies, which can change the composition of K ATP channels [26].…”
Section: Discussionmentioning
confidence: 92%